On distributed snapshot algorithms - Letian He; Yongqiang Sun (Advances in parallel and distributed computing : March 19-21, 1997, Shanghai, China : proceedings, 1997)
Snapshot algorithms are fundamental for many distributed applications and must often be executed repeatedly. We present three snapshot algorithms. The first one is based on the assumption of global time, it computes channel states using several schemes. Taking consistent cut for global time instant, we show that the algorithm is applicable for existing snapshot algorithms. The second one is a real token passing based algorithm for non-FIFO asynchronous distributed systems. Its message complexity of control messages is O(n). The last algorithm is the repeated version of the second one. Using this algorithm, processes can get consistent global states at their convenience concurrently.